Confining Tiny MoO2 Clusters into Reduced Graphene Oxide for Highly Efficient Low Frequency Microwave Absorption. Issue 30 (10th June 2020) - Wu, Cao; Chen, Zhaofeng; Wang, Meiling; Cao, Xun; Zhang, Yong; Song, Pin; Zhang, Tianyuan; Ye, Xinli; Yang, Yong; Gu, Weihua; Zhou, Jiadong; Huang, Yizhong
Abstract: Herein, a supermolecular‐scale cage‐confinement pyrolysis strategy is proposed to build two dielectric electromagnetic wave absorbents, in which MoO2 nanoparticles are sandwiched uniformly between porous carbon shells and reduced graphene oxide (RGO). Both sandwich structures are derived from hybrid hydrogels doped by two different crosslinkers (with/without oxygen bridge), which can precisely confine Mo source (e.g., PMo12 ). Without adding magnetic components, both absorbents exhibit excellent low frequency absorption performance in combination with electrically tunable ability and enhanced reflection loss value, which is superior over other relative 2D dielectric absorbers and satisfies the requirements of portable electronics. Notably, introducing oxygen bridges in the crosslinker generates a more stable confining configuration, which in turn renders its corresponding derivative exhibiting an extra multifrequency electromagnetic wave absorption trait. The intrinsic electromagnetic wave adjustment mechanism of the ternary hybrid absorbent is also explored. The result reveals that the elevated electromagnetic wave absorbing property is attributed to moderate attenuation constant and glorious impendence matching. The cage‐confinement pyrolysis route to fabricate 2D MoO2 ‐based dielectric electromagnetic wave absorbents opens a new path for the design of electromagnetic wave absorbents used in multi/low frequency. Abstract : Uniform MoO2 clusters sandwiched between porous carbon shells and reduced graphene oxide support are realized by a supermolecule cage‐confinement pyrolysis route. Results show that the introduction of different crosslinkers into hydrogel precursors have different adjustment effects on the 2D adsorbent products. Besides, the oxygen bridge‐containing precursor derived adsorbent exhibits an extra multifrequency electromagnetic wave absorption trait, superior over other relative adsorbents.